Psychological aspects affecting the venture performance of Indian women entrepreneurs - Imran Saleem; Ambreen Saleem; Aamir Hassan; Mohd Umar Farukh; Hyder Kamran (Cogent Business & Management, 2023)
This study examines the direct and indirect impact of perceived emotional support in enhancing the venture performance of women entrepreneurs through the mediating effect of entrepreneurial persistence and entrepreneurial passion. The data were collected cross-sectionally from 317 women entrepreneurs across the country using a convenience sample. To ensure the constructs' validity and reliability, Cronbach alpha, C.R, and Heterotrait-Monotrait ratio (HTMT) tests were employed. Hypotheses were tested using PLS-SEM. The findings of this study confirm the statistically significant positive direct impact of entrepreneurial passion and persistence on the venture performance of women entrepreneurs. More importantly, entrepreneurial persistence and passion significantly mediate the link between perceived emotional support and venture performance, conforming to a fully mediated relationship. The current study's findings signify the role of emotional support, particularly among Indian women, in enabling them to persist and boosting their passion for venture success. This research adds to the existing body of knowledge by identifying the mediating effect of entrepreneurial persistence and passion on the perceived emotional support and venture performance relationship. Moreover, it contributes to the scant literature on the construct of perceived emotional support of women entrepreneurs and its impact on venture performance.
Keywords: 650; entrepreneurial passion; entrepreneurial persistence; perceived emotional support; venture performance; women entrepreneurs